2015
DOI: 10.18632/oncotarget.3941
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in CLL pathogenesis and cell survival are disrupted by differentiation of CLL B-cells into antibody-secreting cells

Abstract: Recent research has shown that chronic lymphocytic leukemia (CLL) B-cells display a strong tendency to differentiate into antibody-secreting cells (ASCs) and thus may be amenable to differentiation therapy. However, the effect of this differentiation on factors associated with CLL pathogenesis has not been reported. In the present study, purified CLL B-cells were stimulated to differentiate into ASCs by phorbol myristate acetate or CpG oligodeoxynucleotide, in combination with CD40 ligand and cytokines in a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 94 publications
2
14
0
Order By: Relevance
“…Culturing leukemic B-cells in the CD40 system in the presence of IL-10, but not IL-4 or transforming growth factor-β ( 192 ), induced CLL B-cells to switch to IgG and IgA ( 181 ). Isotype switching of CLL B-cells following differentiation into PCs has been observed in several in vitro studies, but CLL B-cells predominantly differentiated into IgM-secreting PCs ( 14 , 18 21 , 193 196 ). Cases of CLL in which the major clone expresses Ig isotypes other than IgM and IgD, for example, IgG or IgA ( 197 , 198 ) are relatively rare (5%) ( 199 ).…”
Section: What Can the Functional Features Of Cll B-cells Tell Us Aboumentioning
confidence: 92%
“…Culturing leukemic B-cells in the CD40 system in the presence of IL-10, but not IL-4 or transforming growth factor-β ( 192 ), induced CLL B-cells to switch to IgG and IgA ( 181 ). Isotype switching of CLL B-cells following differentiation into PCs has been observed in several in vitro studies, but CLL B-cells predominantly differentiated into IgM-secreting PCs ( 14 , 18 21 , 193 196 ). Cases of CLL in which the major clone expresses Ig isotypes other than IgM and IgD, for example, IgG or IgA ( 197 , 198 ) are relatively rare (5%) ( 199 ).…”
Section: What Can the Functional Features Of Cll B-cells Tell Us Aboumentioning
confidence: 92%
“…Higher LEF1 expression was also associated with adverse prognosis in CLL patients (Erdfelder et al ., ; Wu et al ., ). LEF1 expression levels, among other CLL‐pathogenesis‐related factors including ROR1 or PI3K, were shown to decrease when the CLL cells were forced towards differentiation to plasma cells in vitro using phorbol myristate acetate or CpG oligodeoxynucleotide, in combination with a CD40 ligand and cytokines (Gutierrez et al ., ; Ghamlouch et al ., ).…”
Section: The Role Of Wnt Signalling Pathways In Cll Pathogenesismentioning
confidence: 97%
“…Rare subpopulation of CD5 + CD27 + memory B cells could give rise for CLL cells that carry mutated IGHV [11]. It was revealed earlier that expression levels of lymphoid enhancerbinding factor 1 (LEF1), receptor tyrosine kinase-like orphan receptor 1 (ROR1), fibromodulin (FMOD), T-cell leukemia/lymphoma 1 (TCL1), Ataxin (ATXN1), early B-cell factor 1 (EBF1) and p27 are significantly different in CLL cells compared to normal B-cell analogues [18]. In our study, in addition to evaluation of B-cell stage specific TFs mRNA expression, we revealed deregulation in expression of E26-transformation specific (ETS) TFs PU.1 and SPIB in CLL cells.…”
Section: Results and Disscutionmentioning
confidence: 99%